Clinical Applicability and Real-Life Sustainability of ADA/EFP Oral Hygiene Recommendations: A Cross-Sectional Survey Among Dentists - Gulhan Unal; Hande Özyürek; Furkan Özgür (Medical Science and Discovery, 2026)
Objective: Toothbrushing recommendations published by the American Dental Association (ADA) and the European Federation of Periodontology (EFP) are widely accepted in preventive dentistry. However, their real-life applicability and long-term sustainability in routine clinical practice remain unclear. This study aimed to evaluate dentists’ awareness, clinical implementation, and perceptions regarding the applicability and sustainability of ADA/EFP toothbrushing recommendations. Material and Methods: A cross-sectional online survey was conducted among 208 dentists in Türkiye. The questionnaire assessed guideline awareness, oral hygiene education practices, clinical applicability, perceptions of sustainability, and preferred toothbrushing techniques. Descriptive statistics were used to summarize participant characteristics and survey responses. Categorical variables were presented as frequencies and percentages. Results: Only 15.9% of participants reported directly reading the ADA/EFP guidelines. Among dentists familiar with the guidelines, 64.0% considered the recommendations clinically applicable and 68.0% considered them understandable for patients. Overall, 81.8% agreed that increasing technique complexity reduced patient compliance, while 81.8% believed that simpler techniques were more sustainable. The circular/sweeping combination was the most frequently recommended brushing technique (40.4%), whereas simple circular movements were perceived as the most sustainable approach (42.8%). More than half of the participants (53.4%) supported simplifying current guideline recommendations, and 62.0% favored the developing a simpler standardized toothbrushing method. Conclusion: Although dentists generally accept ADA/EFP toothbrushing recommendations, concerns regarding long-term patient adherence and sustainability remain substantial. Dentists appear to favor simpler, patient-centered toothbrushing approaches that may improve long-term compliance. These findings suggest that behavioral sustainability and motor adaptability should be considered alongside technical efficacy when developing future oral hygiene recommendations.